Salt-sensitive hypertension: role of endothelial and vascular dysfunction and sex - Butler, Helen M.; McCrorey, Marice K.; Palygina, Lada; Lacey, Ryan; Van Beusecum, Justin P. (Frontiers in Pharmacology, 2025)
For the last 120 years, the contribution of salt has been identified in the pathophysiological elevation of blood pressure. Since then, both human and experimental murine studies have begun to elucidate the key mechanisms contributing to the development of salt-sensitive hypertension. Numerous mechanisms, including increased plasma volume, sodium retention, impaired autoregulatory capability, inflammation, and endothelial and vascular dysfunction, contribute to deleterious elevations in blood pressure during salt sensitivity. The endothelium plays a critical role in blood flow regulation, renal blood flow, and blood pressure elevations and in migrating immune cells to end-organs, contributing to end-organ damage and fibrosis. In this review, we will consider the clinical studies setting the foundation for the definition of salt-sensitive hypertension, murine models to study endothelial and vascular contributions, and endothelial cell cultures that have shed light on signaling mechanisms. Lastly, we will discuss the sex-dependent physiology and mechanisms contributing to salt-sensitive hypertension development and their clinical implications.